2009
DOI: 10.1007/s11664-009-0824-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oxygen Post-Growth Annealing on Optical and Electrical Properties of PbSe Thin Films

Abstract: PbSe thin films grown on (111)-oriented Si substrates by molecular-beam epitaxy were annealed under an oxygen atmosphere with a variety of temperatures and times. The photoluminescence intensity from the sample annealed at 350°C for 2 h was increased by 400-fold with frontside pumping and increased by 40-fold with backside pumping, respectively, in comparison with the as-grown sample. Furthermore, the mobility was increased twofold after annealing. Such large photoluminescence increases and mobility improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…The inuence of resistance on the detectivity was analysed, and was summarized in Table 1. Based on the p-n charge separation model for the enhanced photoconduction detection mechanism, 33 the resistance of PbSe detector was regulated by the thickness of PbSeO 3 , 16 The typical frequency response of the optimized VPD-PbSe detector was shown in Fig. 8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inuence of resistance on the detectivity was analysed, and was summarized in Table 1. Based on the p-n charge separation model for the enhanced photoconduction detection mechanism, 33 the resistance of PbSe detector was regulated by the thickness of PbSeO 3 , 16 The typical frequency response of the optimized VPD-PbSe detector was shown in Fig. 8.…”
Section: Resultsmentioning
confidence: 99%
“…These aws are precluding seriously the development of CBD technology and communalization of uncooled lead-salts FPA imagers. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] During last 20 years, an innovative technology named VPD technology was developed by Spanish MoD laboratories (CIDA) and New Infrared Technologies, S.L. (NIT).…”
Section: Introductionmentioning
confidence: 99%
“…It is a familiar experimental fact [49][50][51][52][53][54][55][56][57][58][59] , although the mechanism of oxygen photosensitization has not yet been fully clarified.…”
Section: Surface Morphology and Elemental Compositionmentioning
confidence: 99%
“…39,40,69 The molecular beam epitaxy (MBE) grown monocrystalline PbSe on CaF 2 /Si(111) heterostructure by Li et al 41 showed majority carriers mobility of 647 cm 2 V À1 s À1 and 9.875 Â 10 3 cm 2 V À1 s À1 respectively at 300 K and 77 K, which increased to 1.073 Â 10 3 cm 2 V À1 s À1 and 29.912 Â 10 3 cm 2 V À1 s À1 with an in situ surface treatment. Zhao et al 42 indicated the annealing effect on mobility for a similar structure, where PbSe monocrystalline film showed p-type carrier mobility of 400 cm 2 V À1 s À1 and 1.05 Â 10 4 cm 2 V À1 s À1 respectively at 300 K and 77 K, which increased to 530 cm 2 V À1 s À1 and 2.19 Â 10 4 cm 2 V À1 s À1 after annealing at 300 1C for 2 hours. 42 Tetyorkin et al 43 reported the n-type mobility of monocrystalline PbSe film as 1.5 Â 10 4 cm 2 V À1 s À1 at 77 K, using the thermal evaporation technique.…”
Section: Introductionmentioning
confidence: 98%
“…Zhao et al 42 indicated the annealing effect on mobility for a similar structure, where PbSe monocrystalline film showed p-type carrier mobility of 400 cm 2 V À1 s À1 and 1.05 Â 10 4 cm 2 V À1 s À1 respectively at 300 K and 77 K, which increased to 530 cm 2 V À1 s À1 and 2.19 Â 10 4 cm 2 V À1 s À1 after annealing at 300 1C for 2 hours. 42 Tetyorkin et al 43 reported the n-type mobility of monocrystalline PbSe film as 1.5 Â 10 4 cm 2 V À1 s À1 at 77 K, using the thermal evaporation technique.…”
Section: Introductionmentioning
confidence: 98%